A composite solid electrolyte composition and its preparation method and application
By modifying the inorganic nanofillers with polydopamine and anchoring them in the polymer cross-linking network, the problem of improving the ionic conductivity and mechanical strength of solid electrolytes in all-solid-state lithium-ion batteries is solved, and at the same time, the good dispersion and green preparation of inorganic nanofillers are achieved, which improves the cycle stability and safety of the battery.
Patent Information
- Application Number
- CN202211287798.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-20
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2042-10-20
AI Technical Summary
The solid electrolytes of existing all-solid lithium-ion batteries are difficult to effectively disperse inorganic nanofillers while improving the ionic conductivity and mechanical strength. In addition, harmful organic solvents are often used during the preparation process, resulting in environmental pollution and health hazards.
By modifying the inorganic nanofiller with a compound containing carbon-carbon double bonds and reactive groups, anchoring it to the polymer cross-linking network, a three-dimensional lithium ion transport channel is constructed, the dispersion of the inorganic nanofiller is improved, and the use of organic solvents is abolished.
High ionic conductivity, low interfacial impedance and excellent cycling stability are achieved, while avoiding the use of harmful organic solvents, and achieving green preparation of composite solid electrolytes.
Smart Images

Figure CN115621535B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a composite solid electrolyte composition and a preparation method and application thereof. Background Art
[0002] All-solid-state lithium-ion batteries are expected to replace currently commercial lithium-ion batteries in the future due to their advantages such as high safety and high energy density.
[0003] The realization of excellent electrochemical performance of all-solid-state lithium-ion batteries requires that its core - solid electrolyte has high ionic conductivity and excellent electrolyte / electrode interface contact. Solid polymer electrolytes have good flexibility and excellent contact with the positive electrode, but their ionic conductivity is low, mechanical strength is insufficient, and they cannot inhibit the growth of lithium dendrites. At present, by adding inorganic nanoparticles to solid polymer electrolytes to construct composite solid electrolytes, the mechanical strength of composite solid electrolytes can be improved while improving ionic conductivity. However, due to the large surface energy difference between inorganic nanoparticles and polymer matrices, inorganic nanoparticles tend to aggregate into clusters in the polymer matrix, which seriously affects the full function of inorganic nanoparticles. In addition, harmful organic solvents are often used to dissolve the components in the preparation process of composite solid electrolytes, which will cause environmental pollution and endanger the health of related operators.
[0004] Using the reaction between the functional groups of the polymer matrix, in-situ cross-linking and polymerizing polymers is one of the means to achieve excellent electrochemical properties such as high ionic conductivity of composite solid electrolytes. In patent CN112820938A, an amino-containing ionic liquid is cross-linked with PEGDE and the like, and then mixed with PEO, lithium salt, ionic liquid, etc., to prepare an ion gel electrolyte with excellent properties such as high ionic conductivity in situ. In patent CN113316858A, an ionic liquid self-polymerizes into a polyionic liquid, and is mixed with PEO, lithium salt, and oxide-based solid electrolytes to prepare a salt-doped polymer hybrid solid electrolyte with excellent electrochemical properties.
[0005] The above cases all emphasize the importance of in-situ cross-linking polymerization in improving the electrochemical performance of solid electrolytes, but all ignore the dispersibility of inorganic nanofillers in the polymer matrix and the disadvantages of using organic solvents. To this end, it is necessary to find a suitable solution to modify the inorganic nanofillers, and by adjusting the preparation method, on the basis of giving full play to the advantages of in-situ cross-linking polymerization, improve the dispersibility of inorganic nanofillers in the polymer matrix, make them fully contact with the polymer matrix, and eliminate the harm caused by organic solvents.
[0006] Therefore, it is an urgent problem to be solved in the art to develop an electrolyte with good inorganic nanofiller dispersibility, high ionic conductivity of lithium ion batteries, low interfacial impedance, good cycle stability and no need to add organic solvents. Summary of the invention
[0007] In view of the shortcomings of the prior art, the present invention aims to provide a composite solid electrolyte composition and its preparation method and application. The composite solid electrolyte composition uses polydopamine and a compound containing a carbon-carbon double bond and a reactive group to modify an inorganic nanofiller, anchors the inorganic nanofiller in a polymer cross-linked network, and constructs a three-dimensional lithium ion transmission channel. On the one hand, while enhancing the mechanical strength of the solid polymer electrolyte, it improves the dispersibility of the inorganic nanofiller in the polymer matrix and improves the ionic conductivity and cycle stability of the lithium ion battery; on the other hand, it eliminates the use of harmful organic solvents and realizes the green preparation of the composite solid electrolyte.
[0008] To achieve this object, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a composite solid electrolyte composition, comprising a polymer matrix, a lithium salt, a modified inorganic nanofiller and an initiator; the polymer matrix comprises a polymer containing a carbon-carbon double bond; the modified inorganic nanofiller comprises an inorganic nanofiller, a polydopamine coating layer and a characteristic layer from the inside to the outside; the material of the characteristic layer comprises a compound containing a carbon-carbon double bond and a reactive group.
[0010] In the present invention, inorganic nanofillers are modified by using polydopamine and compounds containing carbon-carbon double bonds and reactive groups, and a polymer matrix containing carbon-carbon double bonds is used at the same time, thereby improving the problem of high interface impedance between the solid electrolyte and the positive and negative electrodes; at the same time, the modified inorganic nanofillers are connected to the polymer matrix through covalent bonds, and the inorganic nanofillers are anchored in the polymer cross-linking network, thereby improving the dispersibility of the inorganic nanofillers in the polymer matrix, and the constructed lithium ion rapid transmission network channel can give full play to the role of the inorganic nanofillers in the polymer matrix, thereby achieving high ionic conductivity, low interface impedance and other properties, and the assembled all-solid-state lithium ion battery has excellent cycle stability.
[0011] Preferably, the polymer matrix comprises at least one of polyethylene glycol acrylates, polypropylene glycol methacrylate, and polypropylene glycol dimethacrylate.
[0012] Preferably, the polyethylene glycol acrylates include at least one of polyethylene glycol methacrylate, polyethylene glycol dimethacrylate, polyethylene glycol diacrylate, polyethylene glycol methyl ether acrylate, polyethylene glycol methyl ether methacrylate, and ethoxylated trimethylolpropane triacrylate; more preferably polyethylene glycol methyl ether methacrylate.
[0013] Preferably, the number average molecular weight of the polymer matrix is 300-1000, for example, 350, 400, 450, 500, 550, 600, 650, 700, 750, 800, 850, 900, etc.
[0014] Preferably, the initiator comprises a photoinitiator and / or a thermal initiator.
[0015] In the present invention, the selection of the initiator is determined according to the type of polymer matrix. Among them, the thermal initiator includes but is not limited to azobisisobutyronitrile; the photoinitiator includes but is not limited to 1-hydroxycyclohexylphenyl ketone.
[0016] Preferably, based on the volume of the polymer matrix being 1 mL, the amount of the initiator used is 1 to 4 mg, for example, 1 mg, 2 mg, 3 mg, 4 mg, etc.
[0017] Preferably, the lithium salt includes at least one of lithium perchlorate, lithium hexafluorophosphate, lithium difluorooxalatoborate, lithium trifluoromethanesulfonate, lithium bis(trifluoromethanesulfonyl imide), lithium tetrafluoroborate, lithium dioxalatoborate, and lithium nitrate, and more preferably lithium bis(trifluoromethanesulfonyl imide).
[0018] Preferably, the molar ratio of the structural units of the polymer matrix to the lithium salt is (8-20):1, for example, it can be 8.5:1, 9:1, 9.5:1, 10:1, 10.5:1, 11:1, 11.5:1, 12:1, 12.5:1, 13:1, 13.5:1, 14:1, 14.5:1, 15:1, 15.5:1, 16:1, 16.5:1, 17:1, 17.5:1, 18:1, 18.5:1, 19:1, 19.5:1, etc.; more preferably, it is (16-18):1.
[0019] Preferably, the modified inorganic nanofiller is 0.1-60% of the mass of the polymer matrix, for example, it can be 0.5%, 1%, 2%, 4%, 8%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 18%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, etc.; preferably, it is 10-15%.
[0020] Preferably, the inorganic nanofiller comprises an inert inorganic nanofiller and / or an ion conductor inorganic nanofiller.
[0021] Preferably, the inert inorganic nanofiller comprises at least one of magnesium oxide, aluminum oxide, titanium oxide, iron oxide, silicon oxide or boron nitride.
[0022] Preferably, the ion conductor inorganic nanofiller includes at least one of a sodium superion conductor, a perovskite ion conductor, a garnet ion conductor, a sulfide-based solid electrolyte or a halogen solid electrolyte; preferably a garnet ion conductor.
[0023] Preferably, the particle size of the inorganic nanofiller is 250-350 nm, for example, 280 nm, 300 nm, 320 nm, 340 nm, etc.
[0024] In the present invention, the chemical formula of the garnet-type ion conductor is Li 6.4 LqCy 1.4 Ta 0.6 O 12 (LLZTO).
[0025] Preferably, the mass of the polydopamine is 2-5% of the inorganic nanofiller, for example, it can be 2.2%, 2.4%, 2.6%, 2.8%, 3%, 3.2%, 3.4%, 3.6%, 3.8%, 4%, 4.2%, 4.4%, 4.6%, 4.8%, etc., and more preferably 4.5-5%.
[0026] Preferably, the reactive group comprises at least one of an acyl halide, a carboxyl group or an ester group.
[0027] Preferably, the material of the characteristic layer includes at least one of methacryloyl chloride, 2-ethylacryloyl chloride, acryloyl chloride, acrylic acid, methacrylic acid, acrylate or methacrylate; more preferably methacryloyl chloride.
[0028] Preferably, the volume mass ratio of the characteristic layer material to the inorganic nanofiller coated with polydopamine is (0.5-4):1, wherein the specific value of (0.5-4) can be, for example, 0.8, 1, 1.2, 1.4, 1.6, 1.8, 2, 2.2, 2.4, 2.6, 2.8, 3, 3.2, 3.4, 3.6, 3.8, etc., and is further preferably (1-2):1.
[0029] Preferably, the modified inorganic nanofiller is prepared by the following method, which comprises:
[0030] (1) mixing a polydopamine precursor with an inorganic nanofiller to obtain a polydopamine-coated inorganic nanofiller;
[0031] (2) reacting the polydopamine-coated inorganic nanofiller obtained in step (1) with the material of the characteristic layer to obtain the modified inorganic nanofiller.
[0032] In the present invention, the percentage of the mass of polydopamine to the mass of the inorganic nanofiller refers to the percentage of the mass of the polydopamine precursor to the mass of the inorganic nanofiller.
[0033] Preferably, the polydopamine precursor in step (1) comprises dopamine hydrochloride.
[0034] Preferably, the mixing in step (1) is carried out in the presence of air.
[0035] Preferably, the mixing in step (1) is carried out under weak alkaline conditions.
[0036] Preferably, the mixing time in step (1) is 20 to 28 hours, for example, 22 hours, 24 hours, 26 hours, etc.
[0037] Preferably, the mixing speed in step (1) is 400-600 rpm, for example, 450 rpm, 500 rpm, 550 rpm, etc.
[0038] Preferably, the mixing temperature in step (1) is room temperature.
[0039] Preferably, the mixing in step (1) is carried out in a solvent.
[0040] Preferably, the solvent includes but is not limited to methanol.
[0041] Preferably, step (1) further comprises washing and / or drying steps after the mixing.
[0042] Preferably, the reaction temperature in step (2) is room temperature.
[0043] Preferably, the reaction time of step (2) is 40 to 50 h, for example, 42 h, 44 h, 46 h, 48 h, etc.
[0044] Preferably, the reaction in step (2) is carried out in the presence of a protective gas.
[0045] Preferably, the protective gas includes but is not limited to nitrogen.
[0046] Preferably, the specific steps of the reaction in step (2) include: mixing the polydopamine-coated inorganic nanofiller with a solvent, ultrasonically dispersing, adding triethylamine and stirring evenly at a temperature of 0° C. in the presence of a protective gas, dripping the material of the characteristic layer for 20 to 40 minutes, then reacting at room temperature for 40 to 50 hours, washing and drying to obtain the modified inorganic nanofiller.
[0047] In a second aspect, the present invention provides a method for preparing the composite solid electrolyte composition according to the first aspect, the preparation method comprising:
[0048] The polymer matrix, lithium salt, modified inorganic nanofiller and initiator are mixed to obtain the composite solid electrolyte composition.
[0049] Preferably, the mixing step specifically includes: pre-mixing the polymer matrix, the lithium salt and the modified inorganic nanofiller, ultrasonically dispersing for 0.5 to 2 hours (for example, it can be 0.8 hours, 1 hour, 1.5 hours, etc.), stirring at room temperature for 10 to 12 hours (10 hours, 11 hours, 12 hours), continuing ultrasonically dispersing for 0.5 to 2 hours (for example, it can be 0.8 hours, 1 hour, 1.5 hours, etc.), adding an initiator, and stirring at room temperature for 1 to 3 hours (for example, it can be 1.5 hours, 2 hours, 2.5 hours) to obtain the composite solid electrolyte composition.
[0050] In a third aspect, the present invention provides an all-solid-state lithium-ion battery, comprising a positive electrode, a composite solid electrolyte and a negative electrode stacked in sequence; the composite solid electrolyte comprises the composite solid electrolyte composition as described in the first aspect.
[0051] Preferably, the positive electrode comprises a lithium iron phosphate positive electrode plate.
[0052] Preferably, the negative electrode comprises a lithium sheet.
[0053] Preferably, the all-solid-state lithium-ion battery also includes a CR2032 button-type battery case.
[0054] In a fourth aspect, the present invention provides a method for preparing the all-solid-state lithium-ion battery according to the third aspect, the preparation method comprising:
[0055] The composite solid electrolyte composition as described in the first aspect is coated on the surface of the positive electrode and the negative electrode respectively, and then assembled and subjected to in-situ polymerization reaction to obtain the all-solid-state lithium-ion battery.
[0056] Preferably, the volume of the composite solid electrolyte composition coated on the surface of the positive electrode and the negative electrode is independently 25 to 750 μL, for example, it can be 30 μL, 40 μL, 50 μL, 60 μL, 70 μL, 80 μL, 90 μL, 100 μL, 200 μL, 300 μL, 400 μL, 500 μL, 600 μL, 700 μL, etc., preferably 30 to 100 μL.
[0057] Preferably, the assembling comprises packaging the assembled positive electrode, composite solid electrolyte, and negative electrode in a CR2032 button battery shell.
[0058] In the present invention, the all-solid-state lithium-ion battery is obtained. When the in-situ polymerization reaction is thermally initiated, the reaction temperature is 60 to 120°C, for example, 70°C, 80°C, 90°C, 100°C, 110°C, etc., and more preferably 60 to 80°C; the reaction time is 1 to 5h, for example, 2h, 3h, 4h, etc., and more preferably 2 to 4h.
[0059] In the present invention, by adopting a polymer matrix containing carbon-carbon double bonds and introducing carbon-carbon double bonds on the surface of an inorganic nanofiller, an all-solid-state lithium-ion battery prepared by in-situ polymerization is beneficial to reducing interface impedance, improving the ionic conductivity and discharge specific capacity of the all-solid-state lithium-ion battery, and maintaining a stable long cycle of the all-solid-state lithium-ion battery.
[0060] In a fifth aspect, the present invention provides an energy storage device, which includes the composite solid electrolyte composition as described in the first aspect and / or the all-solid-state lithium-ion battery as described in the third aspect.
[0061] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0062] Compared with the prior art, the present invention has the following beneficial effects:
[0063] The composite solid electrolyte composition provided by the present invention adopts polydopamine and a compound containing a carbon-carbon double bond and a reactive group to modify an inorganic nanofiller, anchors the inorganic nanofiller in a polymer cross-linked network, constructs a three-dimensional lithium ion transmission channel, enhances the mechanical strength of the solid polymer electrolyte, improves the dispersibility of the inorganic nanofiller in the polymer matrix, is beneficial to the suppression of lithium dendrites, and improves the ion conductivity and cycle stability of the lithium ion battery; and avoids the use of harmful organic solvents, realizes the green preparation of the composite solid electrolyte, and the thickness of the composite solid electrolyte is controllable, so that an ultra-thin composite solid electrolyte can be prepared. BRIEF DESCRIPTION OF THE DRAWINGS
[0064] Figure 1 This is a schematic structural diagram of the composite solid electrolyte composition provided by the present invention. DETAILED DESCRIPTION
[0065] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0066] Preparation Example 1
[0067] A modified inorganic nanofiller, wherein the modified inorganic nanofiller comprises a garnet-type ion conductor Li 6.4 Ln3Z 1.4 Ta 0.6 O 12 (LLZTO, 300nm, Shenzhen Huaxin New Materials Technology Co., Ltd.), a polydopamine (PDA) coating layer and a characteristic layer; the mass of the polydopamine is 4.8% of the mass of LLZTO, the material of the characteristic layer is methacryloyl chloride (MAC), and the volume mass ratio of MAC to PDA-LLZTO is 1:1.
[0068] The preparation method of the modified inorganic filler comprises the following steps:
[0069] (1) 145.2 mg Tris (≥99.9%, T110599, Aladdin reagent) was added to 100 mL anhydrous methanol (AR, 80080418, Sinopharm reagent), stirred evenly, 240 mg dopamine hydrochloride (98%, D103111, Aladdin reagent) was added, stirred evenly, 5 g LLZTO was added, and magnetic stirring was carried out at 500 rpm for 24 h at room temperature. During the stirring process, the solution was ensured to be in contact with air. After the stirring was completed, the solution was filtered and washed with methanol for several times until the filtrate was clear and transparent. Finally, the solid was vacuum dried at 80°C for 12 h to obtain a polydopamine-coated garnet-type ion conductor (PDA-LLZTO).
[0070] (2) 0.3 g of the PDA-LLZTO obtained in step (1) was added to 5 mL of dichloromethane (AR, D116144, Aladdin reagent), and after being dispersed evenly by ultrasonic stirring, the solution was kept at 0°C in an ice-water bath, and 0.3 mL of triethylamine (99%, T103285, Aladdin reagent) was added under nitrogen flow. After stirring evenly, 0.3 mL of methacryloyl chloride (95%, M109517, Aladdin reagent) was slowly added dropwise within 30 min. After the addition was completed, the solution was heated to room temperature and magnetically stirred for 48 h under nitrogen flow at room temperature, followed by centrifugal washing with anhydrous ethanol for 6 times, and finally placed in a vacuum drying oven at 60°C for 24 h to obtain the modified inorganic nanofiller (MAC-PDA-LLZTO).
[0071] Preparation Example 2
[0072] A modified inorganic filler, which differs from Preparation Example 1 only in that the mass of the polydopamine is 2% of the mass of LLZTO, and other raw materials, dosages and preparation methods are the same as those in Preparation Example 1.
[0073] Preparation Example 3
[0074] A modified inorganic filler, which differs from Preparation Example 1 only in that the mass of the polydopamine is 5% of the mass of LLZTO, and other raw materials, dosages and preparation methods are the same as those in Preparation Example 1.
[0075] Preparation Example 4
[0076] A modified inorganic filler, which differs from Preparation Example 1 only in that the volume mass ratio of MAC to PDA-LLZTO is 0.5:1, and other raw materials, amounts and preparation methods are the same as those in Preparation Example 1.
[0077] Preparation Example 5
[0078] A modified inorganic filler, which differs from Preparation Example 1 only in that the volume mass ratio of MAC to PDA-LLZTO is 4:1, and other raw materials, amounts and preparation methods are the same as those in Preparation Example 1.
[0079] Preparation Example 6
[0080] A modified inorganic filler, which differs from Preparation Example 1 only in that the volume mass ratio of MAC to PDA-LLZTO is 5:1, and other raw materials, amounts and preparation methods are the same as those in Preparation Example 1.
[0081] Preparation Example 7
[0082] A modified inorganic filler, which differs from Preparation Example 1 only in that the volume mass ratio of MAC to PDA-LLZTO is 0.2:1, and other raw materials, amounts and preparation methods are the same as those in Preparation Example 1.
[0083] Comparative Preparation Example 1
[0084] A modified inorganic filler, which differs from Preparation Example 1 only in that MAC is replaced by an equal amount of polyethyleneimine, and other raw materials, amounts and preparation methods are the same as those in Preparation Example 1.
[0085] Comparative Preparation Example 2
[0086] A modified inorganic filler, which differs from Preparation Example 1 only in that the polydopamine is replaced by an equal amount of polyethyleneimine, and in the preparation method, dopamine hydrochloride is replaced by an equal amount of polyethyleneimine, and other raw materials, amounts and preparation methods are the same as those in Preparation Example 1.
[0087] Example 1
[0088] The present embodiment provides a composite solid electrolyte composition, which includes polyethylene glycol methyl ether methacrylate (PEGMEMA, average molecular weight is about 475, Aladdin, P109711), lithium bis(trifluoromethanesulfonimide) (LiTFSI), modified inorganic nanofiller MAC-PDA-LLZTO (Preparation Example 1) and AlBN; the molar ratio of the structural unit of the PEGMEMA to LiTFSI is 18:1, the mass of the MAC-PDA-LLZTO is 12% of the mass of the PEGMEMA; the amount of the AlBN is 9.5 mg (concentration 2 mg / mL).
[0089] The present embodiment provides a preparation method of the composite solid electrolyte composition, which comprises: dissolving 1.81 g of LiTFSI (99%, B102576, Aladdin reagent) in 5 g of PEGMEMA (average molecular weight of about 475, P109711, Aladdin reagent) to form a solution of EO:Li=18:1, then adding 0.6 g of MAC-PDA-LLZTO, ultrasonicating for 1 hour, magnetically stirring at room temperature for 12 hours, then ultrasonicating again for 1 hour, and finally adding 9.5 mg (2 mg / ml) of thermal initiator AlBN, and magnetically stirring at room temperature for 2 hours to obtain the composite solid electrolyte composition.
[0090] Example 2
[0091] This embodiment provides a composite solid electrolyte composition, which differs from Example 1 only in that the modified inorganic nanofiller MAC-PDA-LLZTO is the modified inorganic nanofiller provided in Preparation Example 2, and other raw materials, amounts and preparation methods are the same as those in Example 1.
[0092] Example 3
[0093] This embodiment provides a composite solid electrolyte composition, which differs from Example 1 only in that the modified inorganic nanofiller MAC-PDA-LLZTO is the modified inorganic nanofiller provided in Preparation Example 3, and other raw materials, amounts and preparation methods are the same as those in Example 1.
[0094] Example 4
[0095] This embodiment provides a composite solid electrolyte composition, which differs from Example 1 only in that the modified inorganic nanofiller MAC-PDA-LLZTO is the modified inorganic nanofiller provided in Preparation Example 4, and other raw materials, amounts and preparation methods are the same as those in Example 1.
[0096] Example 5
[0097] This embodiment provides a composite solid electrolyte composition, which differs from Example 1 only in that the modified inorganic nanofiller MAC-PDA-LLZTO is the modified inorganic nanofiller provided in Preparation Example 5, and other raw materials, amounts and preparation methods are the same as those in Example 1.
[0098] Example 6
[0099] This embodiment provides a composite solid electrolyte composition, which is different from Example 1 only in that the mass of MAC-PDA-LLZTO is 10% of the mass of PEGMEMA, and other raw materials, amounts and preparation methods are the same as those in Example 1.
[0100] Example 7
[0101] This embodiment provides a composite solid electrolyte composition, which is different from Example 1 only in that the mass of MAC-PDA-LLZTO is 15% of the mass of PEGMEMA, and other raw materials, amounts and preparation methods are the same as those in Example 1.
[0102] Example 8
[0103] This embodiment provides a composite solid electrolyte composition, which is different from Example 1 only in that the mass of MAC-PDA-LLZTO is 60% of the mass of PEGMEMA, and other raw materials, amounts and preparation methods are the same as those in Example 1.
[0104] Example 9
[0105] This embodiment provides a composite solid electrolyte composition, which differs from Example 1 only in that the modified inorganic nanofiller MAC-PDA-LLZTO is the modified inorganic nanofiller provided in Preparation Example 6, and other raw materials, amounts and preparation methods are the same as those in Example 1.
[0106] Example 10
[0107] This embodiment provides a composite solid electrolyte composition, which differs from Example 1 only in that the modified inorganic nanofiller MAC-PDA-LLZTO is the modified inorganic nanofiller provided in Preparation Example 7, and other raw materials, amounts and preparation methods are the same as those in Example 1.
[0108] Comparative Example 1
[0109] This comparative example provides a composite solid electrolyte, which is different from Example 1 only in that the composite solid electrolyte does not contain MAC-PDA-LLZTO, and other raw materials, amounts and preparation methods are the same as those in Example 1.
[0110] Comparative Example 2
[0111] This comparative example provides a composite solid electrolyte, which differs from Example 1 only in that LLZTO is not modified, and other raw materials, amounts and preparation methods are the same as those in Example 1.
[0112] Comparative Example 3
[0113] This comparative example provides a composite solid electrolyte, which differs from Example 1 only in that MAC-PDA-LLZTO is replaced with PDA-LLZTO obtained in Preparation Example 1, and other raw materials, amounts and preparation methods are the same as those in Example 1.
[0114] Comparative Example 4
[0115] This comparative example provides a composite solid electrolyte, which is different from Example 1 only in that the composite solid electrolyte does not contain an initiator, and other raw materials and amounts are the same as those in Example 1.
[0116] The preparation method of the composite solid electrolyte comprises: dissolving PEGMEMA, LiTFSI and MAC-PDA-LLZTO in anhydrous acetonitrile, and magnetically stirring at room temperature for 12 hours to obtain the composite solid electrolyte.
[0117] Comparative Example 5
[0118] This comparative example provides a composite solid electrolyte composition, which differs from Example 1 only in that the modified inorganic nanofiller MAC-PDA-LLZTO is the modified inorganic nanofiller provided in Comparative Preparation Example 1, and other raw materials, amounts and preparation methods are the same as those in Example 1.
[0119] Comparative Example 6
[0120] This comparative example provides a composite solid electrolyte composition, which differs from Example 1 only in that the modified inorganic nanofiller MAC-PDA-LLZTO is the modified inorganic nanofiller provided in Comparative Preparation Example 2, and other raw materials, amounts and preparation methods are the same as those in Example 1.
[0121] Comparative Example 7
[0122] This comparative example provides a composite solid electrolyte composition, which differs from Example 1 only in that LLZTO is not modified in the composite solid electrolyte composition, and includes methacryloxypropyltrimethoxysilane in an equal molar amount to MAC, and other raw materials, amounts and preparation methods are the same as those in Example 1.
[0123] Application Example 1
[0124] An all-solid-state lithium-ion battery, comprising a positive electrode sheet (lithium iron phosphate), a composite solid electrolyte (comprising the composite solid electrolyte composition provided in Example 1) and a negative electrode sheet (lithium sheet); a preparation method of the all-solid-state lithium-ion battery comprising: taking 30 μL of the composite solid electrolyte composition provided in Example 1 and dropping it on a metal lithium sheet with a diameter of 16 mm, then taking 30 μL and dropping it on a lithium iron phosphate positive electrode sheet (LFP) with a diameter of 14 mm to wet the LFP, and finally quickly covering the LFP with slurry on the metal lithium with slurry to form a Li / slurry / slurry / LFP composite structure, and encapsulating it in a CR2032 button battery shell, heating it at 70° C. for 2 h, completing in-situ crosslinking of the polymer and anchoring of MAC-PDA-LLZTO, and obtaining the all-solid-state lithium-ion battery.
[0125] Application Examples 2 to 10
[0126] An all-solid-state lithium-ion battery, in which the composite solid electrolyte comprises the composite solid electrolyte compositions provided in Examples 2 to 10 respectively, and other materials and preparation methods are the same as those in Application Example 1.
[0127] Application Example 11
[0128] A fully solid-state lithium-ion battery. In the preparation method of the fully solid-state lithium-ion battery, the amount of the composite solid electrolyte composition used is 100 μL (100 μL each for the positive electrode sheet and the negative electrode sheet), and other materials and preparation methods are the same as those in Application Example 1.
[0129] Application Example 12
[0130] A fully solid-state lithium-ion battery. In the preparation method of the fully solid-state lithium-ion battery, the amount of the composite solid electrolyte composition used is 25 μL (25 μL each for the positive electrode sheet and the negative electrode sheet), and other materials and preparation methods are the same as those in Application Example 1.
[0131] Application Example 13
[0132] A fully solid-state lithium-ion battery. In the preparation method of the fully solid-state lithium-ion battery, the amount of the composite solid electrolyte composition used is 750 μL (750 μL each for the positive electrode sheet and the negative electrode sheet), and other materials and preparation methods are the same as those in Application Example 1.
[0133] Application Example 14
[0134] A fully solid-state lithium-ion battery, the preparation method of the fully solid-state lithium-ion battery comprising: stirring the composite solid electrolyte composition obtained in Example 1 evenly, coating it in a polytetrafluoroethylene mold, then heating it at 70°C for 2h, in-situ polymerizing it into a film, assembling the obtained film with lithium iron phosphate and a lithium sheet and encapsulating it in a CR2032 button battery shell to obtain the fully solid-state lithium-ion battery.
[0135] Comparative Application Examples 1 to 3
[0136] An all-solid-state lithium-ion battery, in which the composite solid electrolyte comprises the composite solid electrolyte compositions provided in Comparative Examples 1 to 3 respectively, and other materials and preparation methods are the same as those in Application Example 1.
[0137] Comparative Application Example 4
[0138] A fully solid-state lithium-ion battery, the preparation method of the fully solid-state lithium-ion battery comprising: coating the composite solid-state electrolyte composition obtained in comparative example 4 in a polytetrafluoroethylene mold, drying naturally for 12 hours, and then heating and drying in vacuum at 60°C for 24 hours to obtain a composite solid-state electrolyte membrane, assembling it with lithium iron phosphate and a lithium sheet and encapsulating it in a CR2032 button battery shell to obtain the fully solid-state lithium-ion battery.
[0139] Comparative Application Examples 5 to 7
[0140] An all-solid-state lithium-ion battery, in which the composite solid electrolyte comprises the composite solid electrolyte compositions provided in Comparative Examples 5 to 7, respectively, and other materials and preparation methods are the same as those in Application Example 1.
[0141] Performance Testing
[0142] (1) Ionic conductivity: The positive and negative electrodes in the preparation method of the all-solid-state lithium-ion battery were replaced with two pieces of stainless steel foil as blocking electrodes, and the AC impedance test was performed using the Shanghai Chenhua electrochemical workstation with the frequency range set to 0.1-1 MHz and the amplitude set to 10 mV, and the ionic conductivity test was performed at room temperature (30°C);
[0143] (2) Mechanical properties test: The mechanical properties of the composite solid electrolyte membrane were characterized by stress tensile test. Before the test, the environment of the instrument was dehumidified and the ambient temperature was controlled at 25°C. The composite solid electrolyte membrane to be tested was cut into a size of 50 mm long and 10 mm wide. The tensile speed was set to 6 mm / min and the clamp distance was 20 mm.
[0144] (3) Testing of specific capacity and capacity retention rate: The all-solid-state lithium-ion battery was charged and discharged at a constant current of 60°C and a current density of 0.2C within the range of 2.8 to 4.0V. The initial discharge specific capacity and the discharge specific capacity after 100 cycles were tested, and the capacity retention rate was calculated.
[0145] The specific test results are shown in Table 1:
[0146] Table 1
[0147]
[0148]
[0149] As can be seen from the above table, the composite solid electrolyte composition provided by the present invention uses polydopamine and a compound containing a carbon-carbon double bond and a reactive group to modify the inorganic nanofiller, anchor the inorganic nanofiller in the polymer cross-linked network, construct a three-dimensional lithium ion transmission channel, enhance the mechanical strength of the solid polymer electrolyte, improve the dispersibility of the inorganic nanofiller in the polymer matrix, and is conducive to the suppression of lithium dendrites, thereby improving the ionic conductivity and cycle stability of the lithium ion battery. As can be seen from Application Examples 1 to 8, the ionic conductivity of the composite solid electrolyte is 2 to 3.2×10 -4 S / cm, the tensile strength reaches 46-60MPa, and the all-solid-state lithium ion battery including the composite solid electrolyte has an initial discharge specific capacity of 148.72-158.43mAh / g and a capacity retention rate of 93-98% after 100 cycles.
[0150] By comparing application examples 1 to 3, it can be seen that as the amount of PDA added continues to increase, the ionic conductivity of the composite solid electrolyte gradually increases, and the tensile strength does not differ much. When the amount added reaches a certain value, the ionic conductivity gradually tends to stabilize, which indicates that the more PDA is added, the more PDA is contained on the LLZTO surface and the more complete the coating is, which is beneficial to the subsequent coating of MAC and its anchoring in the cross-linked polymer network. When the PDA coating amount reaches a certain value, continuing to increase the amount of PDA added will only increase the thickness of the coated PDA film, which has little effect on the ionic conductivity and tensile strength.
[0151] By comparing Examples 1, 4, and 5, it can be seen that within a specific range, as the amount of MAC added increases, the ionic conductivity of the composite solid electrolyte gradually increases, and the tensile strength does not change much. The reason for this phenomenon is similar to the reason for the change caused by the increase in PDA, that is, there is also an optimal MAC addition amount, which makes the composite solid electrolyte have the highest ionic conductivity and higher tensile strength. By comparing Application Example 1 with Application Examples 9 and 10, it can be seen that the amount of MAC added is not within the range defined by the present invention, the ionic conductivity of the composite solid electrolyte decreases, the battery capacity retention rate decreases, and the tensile strength of the membrane decreases.
[0152] By comparing application examples 1, 6, 7, and 8, it can be seen that with the increase of modified inorganic nanofillers, the ionic conductivity of the composite solid electrolyte continues to increase. When the addition amount exceeds a certain value, its ionic conductivity decreases instead. This shows that with the increase of inorganic nanofillers, the lithium ion concentration in the composite solid electrolyte continues to increase, and the ionic conductivity will naturally increase. However, excessive addition of inorganic nanofillers will hinder the migration of lithium ions, resulting in a decrease in ionic conductivity. As the amount of inorganic nanofillers added continues to increase, the tensile strength also continues to increase, which shows the characteristics of high strength and mechanical stability of inorganic nanofillers.
[0153] By comparing Application Example 1 with Application Examples 11 to 13, it can be seen that the more slurry is added, the thicker the composite solid electrolyte is, and the longer the lithium ion migration path is, which will lead to a decrease in ionic conductivity and a decrease in discharge specific capacity. A composite solid electrolyte with appropriate thickness can not only maintain good mechanical stability and have sufficient strength to inhibit lithium dendrites, but also provide high ionic conductivity.
[0154] From the comparison between Application Example 1 and Application Example 14, it can be seen that the in-situ polymerized composite solid electrolyte can achieve good contact between the electrolyte and the electrode, low interface impedance, and smoother migration of lithium ions at the interface, thereby achieving high ionic conductivity and discharge specific capacity, and maintaining a stable and long cycle of the all-solid-state lithium-ion battery. However, the preparation of an independent composite solid electrolyte first and then contacting it with the positive and negative electrodes will produce a harder solid-solid contact, high impedance between the electrolyte and the electrode interface, poor contact, and it is difficult to obtain a stable cycle of the all-solid-state lithium-ion battery.
[0155] By comparing Application Example 1 with Comparative Application Examples 1-3, 5-7, it can be seen that the coating of polydopamine and methacryloyl chloride realizes the anchoring of inorganic nanofillers in the polymer matrix, which is due to the covalent bonds and between the double bonds of methacryloyl chloride and the double bonds of the polymer PEGMEMA. The anchoring of the inorganic nanofiller makes it evenly dispersed in PEGMEMA, and at the same time, lithium ions can be quickly transmitted in three-dimensional space along the polymer chain, which significantly improves the ionic conductivity of the composite solid electrolyte. However, when no modified inorganic nanofiller is added, the inorganic nanomaterial is not modified, or the inorganic nanofiller is not modified by a specific material, the ionic conductivity and mechanical strength of the composite solid electrolyte will be reduced.
[0156] By comparing Application Example 1 with Comparative Application Example 4, it can be seen that the composite solid electrolyte prepared by solvent-free and thermal polymerization involved in the present invention has better performance. The use of traditional solution casting method to prepare composite solid electrolyte, on the one hand, affects the construction of PEFMEMA cross-linked network, resulting in the loss of lithium ion transmission network; on the other hand, the residual organic solvent hinders lithium ion transmission, and satisfactory ionic conductivity and mechanical strength cannot be obtained.
[0157] From the comparison between Application Example 1 and Comparative Application Examples 5 to 7, it can be seen that the modification of inorganic nanoparticles and the selection of characteristic layers designed in the present invention promote the interaction between the inorganic nanoparticles and the polymer matrix, thereby improving the dispersibility of the inorganic nanoparticles in the polymer matrix, and ensuring the excellent cycle stability of the all-solid-state battery composed of the composite solid electrolyte composition.
[0158] In summary, the composite solid electrolyte composition provided by the present invention modifies inorganic nanofillers by using polydopamine and a compound containing a carbon-carbon double bond and a reactive group, anchors the inorganic nanofillers in a polymer cross-linked network, and constructs a three-dimensional lithium ion transmission channel. On the one hand, while enhancing the mechanical strength of the solid polymer electrolyte, the dispersibility of the inorganic nanofillers in the polymer matrix is improved, thereby improving the ionic conductivity and cycle stability of the lithium ion battery; on the other hand, the use of harmful organic solvents is eliminated, thereby achieving green preparation of the composite solid electrolyte.
[0159] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A composite solid electrolyte composition, characterized in that: The composite solid electrolyte composition comprises a polymer matrix, a lithium salt, a modified inorganic nanofiller and an initiator; The polymer matrix includes a polymer containing carbon-carbon double bonds; The modified inorganic nanofiller includes an inorganic nanofiller, a polydopamine coating layer and a characteristic layer from the inside to the outside; The material of the characteristic layer includes a compound containing a carbon-carbon double bond and a reactive group; The reactive group includes at least one of an acyl halide, a carboxyl group or an ester group.
2. The composite solid electrolyte composition according to claim 1, characterized in that The polymer matrix includes at least one of polyethylene glycol acrylates, polypropylene glycol methacrylate, and polypropylene glycol dimethacrylate.
3. The composite solid electrolyte composition according to claim 2, characterized in that: The polyethylene glycol acrylates include at least one of polyethylene glycol methacrylate, polyethylene glycol dimethacrylate, polyethylene glycol diacrylate, polyethylene glycol methyl ether acrylate, polyethylene glycol methyl ether methacrylate, and ethoxylated trimethylolpropane triacrylate.
4. The composite solid electrolyte composition according to claim 3, characterized in that: The polyethylene glycol acrylate is polyethylene glycol methyl ether methacrylate.
5. The composite solid electrolyte composition according to claim 1, characterized in that The initiator includes a photoinitiator and / or a thermal initiator.
6. The composite solid electrolyte composition according to claim 1, characterized in that Based on the volume of the polymer matrix being 1 mL, the amount of the initiator used is 1 to 4 mg.
7. The composite solid electrolyte composition according to claim 1, characterized in that: The lithium salt includes at least one of lithium perchlorate, lithium hexafluorophosphate, lithium difluorooxalatoborate, lithium trifluoromethanesulfonate, lithium bis(trifluoromethanesulfonyl imide), lithium tetrafluoroborate, lithium dioxalatoborate, and lithium nitrate.
8. The composite solid electrolyte composition according to claim 7, characterized in that: The lithium salt is lithium bis(trifluoromethanesulfonyl)imide.
9. The composite solid electrolyte composition according to claim 1, characterized in that: The molar ratio of the structural unit of the polymer matrix to the lithium salt is (8-20):
1.
10. The composite solid electrolyte composition according to claim 9, characterized in that: The molar ratio of the structural unit of the polymer matrix to the lithium salt is (16-18):
1.
11. The composite solid electrolyte composition according to claim 1, characterized in that: The modified inorganic nano filler accounts for 0.1-60% of the mass of the polymer matrix.
12. The composite solid electrolyte composition according to claim 11, characterized in that: The modified inorganic nano filler accounts for 10-15% of the mass of the polymer matrix.
13. The composite solid electrolyte composition according to claim 1, characterized in that: The inorganic nanofiller includes an inert inorganic nanofiller and / or an ion conductor inorganic nanofiller.
14. The composite solid electrolyte composition according to claim 13, characterized in that: The inert inorganic nanofiller includes at least one of magnesium oxide, aluminum oxide, titanium oxide, iron oxide, silicon oxide or boron nitride.
15. The composite solid electrolyte composition according to claim 13, characterized in that: The ion conductor inorganic nanofiller includes at least one of a sodium super ion conductor, a perovskite ion conductor, a garnet ion conductor, a sulfide-based solid electrolyte or a halogen solid electrolyte.
16. The composite solid electrolyte composition according to claim 15, characterized in that: The ion conductor inorganic nanofiller is a garnet type ion conductor.
17. The composite solid electrolyte composition according to claim 1, characterized in that: The mass of the polydopamine is 2-5% of the inorganic nano filler.
18. The composite solid electrolyte composition according to claim 17, characterized in that: The mass of the polydopamine is 4.5-5% of the inorganic nanofiller.
19. The composite solid electrolyte composition according to claim 1, characterized in that: The material of the characteristic layer includes at least one of methacryloyl chloride, 2-ethylacryloyl chloride, acryloyl chloride, acrylic acid, methacrylic acid, acrylic ester or methacrylic ester.
20. The composite solid electrolyte composition according to claim 1, characterized in that: The material of the characteristic layer is methacryloyl chloride.
21. The composite solid electrolyte composition according to claim 1, characterized in that: The volume mass ratio of the material of the characteristic layer to the inorganic nanofiller coated with polydopamine is (0.5-4):
1.
22. The composite solid electrolyte composition according to claim 21, characterized in that The volume mass ratio of the material of the characteristic layer to the inorganic nanofiller coated with polydopamine is (1-2):
1.
23. The composite solid electrolyte composition according to claim 1, characterized in that: The modified inorganic nanofiller is prepared by the following method, which comprises: (1) mixing a polydopamine precursor with an inorganic nanofiller to obtain a polydopamine-coated inorganic nanofiller; (2) reacting the polydopamine-coated inorganic nanofiller obtained in step (1) with the material of the characteristic layer to obtain the modified inorganic nanofiller.
24. The composite solid electrolyte composition according to claim 23, characterized in that: The polydopamine precursor in step (1) includes dopamine hydrochloride.
25. The composite solid electrolyte composition according to claim 23, characterized in that: The mixing in step (1) is carried out in the presence of air.
26. The composite solid electrolyte composition according to claim 23, characterized in that: The mixing in step (1) is carried out under weak alkaline conditions.
27. The composite solid electrolyte composition according to claim 23, characterized in that: The mixing time in step (1) is 20 to 28 hours.
28. The composite solid electrolyte composition according to claim 23, characterized in that: The reaction temperature in step (2) is room temperature.
29. The composite solid electrolyte composition according to claim 23, characterized in that: The reaction time of step (2) is 40 to 50 hours.
30. The composite solid electrolyte composition according to claim 23, characterized in that: The reaction in step (2) is carried out in the presence of a protective gas.
31. A method for preparing a composite solid electrolyte composition according to any one of claims 1 to 30, characterized in that: The preparation method comprises: The polymer matrix, lithium salt, modified inorganic nanofiller and initiator are mixed to obtain the composite solid electrolyte composition.
32. An all-solid-state lithium-ion battery, characterized in that: The all-solid-state lithium-ion battery comprises a positive electrode, a composite solid electrolyte and a negative electrode stacked in sequence; The composite solid electrolyte comprises the composite solid electrolyte composition according to any one of claims 1 to 30.
33. The all-solid-state lithium-ion battery according to claim 32, characterized in that: The positive electrode comprises a lithium iron phosphate positive electrode plate.
34. The all-solid-state lithium-ion battery according to claim 32, characterized in that: The negative electrode includes a lithium sheet.
35. A method for preparing an all-solid-state lithium-ion battery according to any one of claims 32 to 34, characterized in that: The preparation method comprises: The composite solid electrolyte composition according to any one of claims 1 to 30 is coated on the surface of the positive electrode and the negative electrode respectively, and then assembled and subjected to in-situ polymerization reaction to obtain the all-solid-state lithium-ion battery.
36. The preparation method according to claim 35, characterized in that: The volumes of the composite solid electrolyte composition coated on the surfaces of the positive electrode and the negative electrode are independently 25 to 750 μL.
37. The preparation method according to claim 36, characterized in that: The volumes of the composite solid electrolyte composition coated on the surfaces of the positive electrode and the negative electrode are independently 30 to 100 μL.
38. An energy storage device, characterized in that: The energy storage device comprises the composite solid electrolyte composition according to any one of claims 1 to 30 and / or the all-solid-state lithium-ion battery according to any one of claims 32 to 34.
Citation Information
Patent Citations
Ionic gel electrolyte with semi-interpenetrating network structure as well as preparation method and application of ionic gel electrolyte
CN112820938A
Hybrid solid electrolyte for all-solid-state battery
CN113316858A
Organic in-situ interface modified solid electrolyte and preparation method thereof
CN113363560A
Composite solid electrolyte membrane, preparation method thereof and all-solid-state lithium metal battery
CN114927753A
Cited By
Composite ceramic solid electrolyte diaphragm material as well as preparation method and application thereof
CN120657376A